Is Kawasaki disease incidence rising in Chandigarh, North India?. Issue 2 (5th October 2010) - Singh, Surjit; Aulakh, Roosy; Bhalla, Anil Kumar; Suri, Deepti; Manojkumar, Rohit; Narula, Nidhi; Burns, Jane C
Abstract : Objective: To estimate incidence of Kawasaki disease (KD) over time among children in the city of Chandigarh, North India. Patients and methods: We analysed records of all children with KD below 15 years of age at the Pediatric Allergy Immunology Unit, Advanced Pediatrics Centre, Post Graduate Institute of Medical Education and Research, Chandigarh, from January 1994 to December 2008. Diagnosis and treatment of KD were based on American Heart Association criteria. Among these cases, children residing in Chandigarh were identified. Yearly incidence was calculated and compared from 1994 to 2008. Results: During this period, 196 children were diagnosed as KD. Of these, 80 (40.8%; 48 boys, 32 girls) resided in Chandigarh. Four among these had coronary artery abnormalities (CAA) on echocardiography, while two had mitral regurgitation. Comparison of yearly data revealed increasing incidence of disease from 0.51 cases in 1994 to 4.54 cases per 100 000 children below 15 years of age in 2007. Majority (93.7%) of cases occurred in children ≤10 years of age with the highest incidence reported in the seventh year of life. Monthly distribution of disease showed two peaks with a maximum number of cases presenting in October followed by a second peak in May with a nadir in the month of February. Conclusion: Increasing incidence of KD in Chandigarh could be due to increasing clinical recognition as a result of greater awareness among paediatricians in the city, or may represent an actual increase in numbers. Striking differences from KD series reported from other countries include the older median age of our patients, low rate of CAA and a different bimodal seasonality, which may be epidemiologic clues to the nature of this vasculitis.